COVID-19 mini-review: D614G mutation as an independent risk-factor to the expression of ACE2 and DPP4 associated increased severity in COVID-19 - Siti Asmaa Mat Jusoh,; Parisa Foroozandeh,; Lee, Yan Fen; Mardani Abdul Halim,; Manoj Kumar Laskmanan,; Shaharum Shamsuddin, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The novel coronavirus 2019 (COVID-19) has struck more than 99 million people worldwide and had claimed more than 2 million lives as of 23 January 2021, which affecting 221 countries/nations. Until now, the pandemic has not shown signals of slowing down, with no proven vaccine in sight. People are speculating on this unprecedented event. It is well documented that the receptor-binding domain (RBD) of the viral spiked S1 glycoprotein directly bind angiotensin-converting enzyme 2 (ACE2) and dipeptidyl-peptidase-4 (DPP4) or CD26 (cluster of differentiation 26) receptors lead to their entry. The latest evidence demonstrated that SAR-CoV-2 possesses genetic heterogeneity, lead to the existence of a new SAR-CoV-2 variant, such as D614G encoded the spiked S1. The mutation involved changes in amino acid sequence of D (aspartic acid) into G (guanine) at position 614. D614G was reported to confer high infectivity and became the dominant form of the virus globally. Interestingly, current evidence found that D614G protein increases its infectivity dependent on the ACE2 receptor, and its co-binding receptor, DPP4. This proclaims implied to COVID-19 high-risk groups; the aging population and the people with comorbidities; hypertension, cardiovascular disease, and diabetes, which constituted the most of lethal cases, that overexpressed ACE2 and DPP4. The review aims to find an association between COVID-19 infectivity and severity relating to D614G mutation with the expression of ACE2 or DPP4 in these groups. We proposed that D614G mutation and expressions of ACE2 and DPP4 were mutually inclusive for increase infectivity, but not severity in COVID-19’s patients.